Analysis of the Implementation of Digitalization of Financial Statements in Micro, Small, and Medium Enterprises - Susilowati, Eni; Andrean Permadi; Sri Hariyanti; Misbahul Munir; Agus Wahyudi (Open Access Indonesia Journal of Social Sciences, 2023)
Micro, small, and medium enterprises (MSMEs) that use a digitalized financial reporting system can gain easier access to financial services. Structured and accurate financial reports can assist them in applying for loans or obtaining financial support from financial institutions or investors. This study aimed to explore the use of digitizing financial reports for MSMEs in Tulungagung Regency, Indonesia. This study is qualitative observational research. The data used in this study are primary data and secondary data. As many as 30 MSMEs in the culinary field, which are still operating in Tulungagung in 2023, were included in this study. MSMEs are not yet optimal in utilizing digitization due to several reasons, including limited MSME resources, lack of understanding, and limited knowledge of MSME owners who may not have sufficient understanding of the benefits and process of digitizing financial statements and fear of data security and confidentiality. MSMEs may worry about the security of their data when using digitization systems, preference for conventional methods, implementation of digitization systems requires adjustment and integration with existing systems in MSMEs, technical challenges such as inadequate technological infrastructure, limited internet access, or lack of technical skills in operating the system can be an obstacle for MSMEs to use digitization of financial statements.